The determinants of life insurance demand in Malaysia during covid-19 pandemic - Poh, Joyce; Liew, Zhi Ling; Tiew, Shin Ying; Toh, Wei Jie; Yong, Jia Yung (2022)
Life insurance is one of the approaches to manage personal financial risk. It can successfully protect the remaining members of the family from loss of income due to the premature death of the family breadwinner, especially with the recent COVID-19 pandemic. The primary objective of this study is to determine the factors that influencing the life insurance demand in Malaysia during the Covid-19 pandemic, based on the theory of reasoned action (TRA). The relationship between perception of life insurance benefits, risk perception, subjective norms, financial literacy, and life insurance demand is analysed. The methodology of this study is quantitative research method. The data collection instrument used to obtain the required information from the primary source was a questionnaire. The researcher used snowball sampling technique from non-probability sampling technique. After determining the reliability of the questionnaire, 480 questionnaires were randomly distributed to Malaysian residents aged 18 years and above from various occupational backgrounds without any gender restrictions. A total of 384 questionnaires were completed and returned. Based on the collected data, the researchers performed descriptive analysis, reliability test, Pearson correlation coefficient analysis and multiple linear regression analysis using SPSS software. The results showed that all independent variables (perception of life insurance benefits, risk perception, subjective norms, and financial literacy) exhibited a significantly positive impact on the dependent variable (life insurance demand). Some limitations and recommendations are included in the study to provide future researchers and life insurance service providers with better ideas to improve the purchasing behaviour of life insurance in Malaysia.